Evaluating life cycle cost and performance comparison between cold in place recycling and reconstruction method - Wan Omar, Wan Imran; Ali, Maisarah (2014)
Many commentators pointed out that large amount of money had been spent in maintaining and sustaining the road pavement every year in Malaysia. The rapid road deterioration and eventual failure from both climatic and vehicle loads impacts have significantly incurred the total cost of road maintenance works. Functional and structural failures of the pavement need to be rehabilitated. Reconstruction work is the conventional method usually used to rehabilitate the structural failures of flexible pavement; meanwhile cold-in place recycling (CIPR) is an alternative method that has been employed in many countries worldwide, including Malaysia.This paper reports part of a two-year programme of research to determine the most-cost effectiveness and best performance of road rehabilitation method in Malaysia. The objective of this paper is to present the outcomes of life cycle cost and performance analysis of mutually exclusive pavement rehabilitation method, i.e. cold-in place recycling (CIPR) and reconstruction method. The life cycle cost and performance of these two pavement rehabilitation methods were evaluated to identify the correlation between the costs incurred against the performance gained. Theoretically a high strength pavement should be able to sustain longer life. From the findings, the CIPR is found to be more cost-effective with superior performance comparing to the reconstruction method. The results also have established that the initial and overall capital cost of reconstruction method is cheaper; however, CIPR is more cost-effective and better performance over two designed life spans, i.e. 5 years and 10 years. Keywords: LCC, performance, CIPR, reconstruction